Projeção e avaliação de uma nova ligadura ortodôntica – análise da força de atrito - Cenci, Jaisson (2019)
Aim: To evaluate and compare the friction of different ligature modes used in orthodontics, and to propose a new ligature model for conventional brackets. Materials and Methods: Samples were randomly divided into 7 experimental groups: Resin H ligature (H3D), designed by the authors of this study and produced in a 3D printer, with conventional bracket; Metal H ligature (HFM), with conventional bracket; Passive self-ligating bracket (SLP); “8” low friction unconventional elastic (LT8), with conventional bracket; Loose conventional metal ligature (MLS), with conventional bracket; Conventional metal ligature fully tightened (MLT), with conventional bracket; Convencional elastic ligature (CEL), with conventional bracket – control. All samples were subjected to mechanical static friction testing using the EMIC DL 2000 universal testing machine to get the maximum force value. Shapiro Wilk test was used to assess the normality requirement. Then the data were submitted to Analysis of Variance (NOVA), one way, and Tykey’s post test. Results: The results obtained showed lower friction value for HFM (0.002 Kg/F), SLP (0.003 Kg/F), e LT8 (0.004 Kg/F) – these did not differ statistically from each other. Followed by H3D (0.020 Kg/F), MLS (0.049 Kg/F), CEL (0.12 Kg/F) e MLT (0.21 Kg/F). Conclusions: The lowest friction value was found for the H metal ligature, which did not differ statistically with the passive self-ligating bracket.